P1369 Mitral regurgitation reduction after transcatheter aortic valve implantation (TAVI). (17th January 2020) - Ostrowska Kaim, E; Stapor, M; Trebacz, J; Sobczynski, R; Konstanty-Kalandyk, J; Wiewiorka, Ł; Nawara-Skipirzepa, J; Musial, R; Zmudka, K; Kapelak, B; Legutko, J
Abstract: BACKGROUND: Concomitant mitral regurgitation (MR) is frequently observed in patients with severe aortic stenosis. Improvement of functional MR after TAVI has previously been reported, although influence of TAVI on organic MR remains unclear. METHODS: We analyzed 136 patients who underwent TAVI in years 2017-2018 in our center. 16 of them had none or trivial preprocedural MR, 80 had mild preprocedural MR (nonsignificant MR group) and 40 had moderate or severe regurgitation (significant MR group). Specific etiology of each significant MR was classified as functional (11 patients), organic or mixed (29 patients). In addition, left ventricular ejection fraction (EF) was assessed using Simpson"s method. Follow-up (discharge) transthoracic echocardiographywas performed 1 to 5 days after TAVI. RESULTS: MR diminished in 33, 9% of patients undergoing TAVI (nonsignificant and significant MR group, p = 0, 0118). Reduction of MR was pronounced in both: functional MR (45, 4%, p = 0, 0152) and organic or mixed etiology (72, 4%, p = 0, 0000). Left ventricular EF did not change after TAVI (p = 0, 976). CONCLUSIONS: Mitral regurgitation decreases significantly after TAVI, regardless of the etiology.